2019
DOI: 10.1111/sjpe.12231
|View full text |Cite
|
Sign up to set email alerts
|

The financial costs of political uncertainty: Evidence from the 2016 US presidential elections

Abstract: The victory of Mr. Donald Trump came as a surprise to a wide range of market participants. Some of the elements of his economic plan were envisaged to affect all US sectors. This paper assesses the reactions of disaggregated US stock market to the 2016 US presidential election results, and possible deregulation that is to follow after his inauguration. We find that the different US sectors were significantly and varyingly influenced by the election result, and were greatly reactive during the days after the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Specifically, the authors demonstrated that S&P 500 firms with pre-existing presidential ties generated higher abnormal returns over a 21-day post-election period and, in addition, during his presidential term, they received more government contracts and were subject to more favorable regulation than nonconnected counterparts. Along these lines, Selmi and Bouoiyour (2020) using an event study methodology, concluded that the election result and the presidential inauguration affected the U.S. stock market in various ways. More precisely, consumer discretionary, energy, industrials, materials, aerospace and defense and real estate sectors exhibited positive reactions, while consumer staples, financial, health care, information technology, communication, and utility sectors were adversely influenced by the election results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, the authors demonstrated that S&P 500 firms with pre-existing presidential ties generated higher abnormal returns over a 21-day post-election period and, in addition, during his presidential term, they received more government contracts and were subject to more favorable regulation than nonconnected counterparts. Along these lines, Selmi and Bouoiyour (2020) using an event study methodology, concluded that the election result and the presidential inauguration affected the U.S. stock market in various ways. More precisely, consumer discretionary, energy, industrials, materials, aerospace and defense and real estate sectors exhibited positive reactions, while consumer staples, financial, health care, information technology, communication, and utility sectors were adversely influenced by the election results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finansal piyasalar ülkedeki makroekonomik, maliye ve para politikaları üzerinde önemli etkiler yaratabilecek siyasi olaylara tepki verme eğilimindedir. Bu siyasi olaylar, bu olayların sonuçlarına göre beklentilerini oluşturan ve revize eden yatırımcılar tarafından izlenmektedir (Selmi & Bouoiyour, 2020). Politik ve ekonomik yansımaları olan olaylar, ilgili ülke piyasasında risk ve getiri üzerinde etkili olmaktadır.…”
Section: Li̇teratürunclassified